Pengaruh Electronic Word Of Mouth (E-Wom) Di Media Sosial Twitter Terhadap Minat Beli Konsumen - Nindita Fajriani; Indrawati . (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
The growth of the food and beverage industry is starting to become one of the pillars of national economic growth and the culinary subsector has contributed 41.4%. Based on 2019 APJII the number of internet users in Indonesia is 64.8% and 56% of social media users. Through social media can make it easier for people to communicate and search for information so that they can create Electronic Word of Mouth (EWOM) as marketing communication, one of which is Sang pisang on Twitter. Consumer purchase intentions are recognized as the effectiveness of Electronic Word of Mouth communication because the amount of consumer experience influences the outcome of consumer attitudes. This study aims to determine whether there is an influence of Electronic Word of Mouth on social media Twitter on consumer buying interest in Sang Banana products. This study EWOM quality, quantity, credibility, and expertise as an independent variable, and consumer buying interest as the dependent variable. Quantitative method, distributing questionnaires to 400 respondents with non-probability sampling techniques. Data analysis techniques using SEM with PLS and test hypotheses. The results of this study are EWOM (quality, quantity, and credibility) significant and positive effect on consumer’s purchase intention. While EWOM's expertise has no significant and positive effect on consumer’s purchase intention.